Pengaruh Faktor Demografi Budaya dan Praktik Pemberian Gizi terhadap Kejadian Stunting pada Balita dengan Pendekatan Transcultural Nursing - Dia Rejeki Utami; Andi Ernawati Manuntungi; Hanriska Awidiya Putri; Erni Agit Ekawati; Yuniarti Ekasaputri Burhanuddin; Evi Kusmayanti; Halisah Halisah (Yayasan Mandar Indonesia, 2026)
Stunting is a chronic nutritional problem among children under five and is influenced by multidimensional factors, including feeding practices, family support, cultural values, and lifestyle. A transcultural nursing approach is relevant because child feeding practices are often shaped by family beliefs, social norms, local culture, and household decision-making patterns. This study aimed to analyze the influence of demographic factors, socio-cultural factors, and nutritional feeding practices on stunting among children under five using a transcultural nursing approach in Mamuju City. This study used an analytic descriptive design with a cross-sectional approach. A total of 76 mothers with children under five from stunting locus public health center areas in Mamuju City were selected using purposive sampling. Data were collected using demographic, socio-cultural, and nutritional feeding practice questionnaires, then analyzed descriptively and through direct effect testing. Most mothers had senior high school education, 35 respondents (46.1%); were employed, 54 respondents (71.1%); had maternal height >150 cm, 71 respondents (93.4%); and 7 children (9.2%) were stunted. Demographic factors significantly influenced nutritional feeding practices but had no direct influence on stunting. Nutritional feeding practices significantly influenced stunting. Socio-cultural factors significantly influenced both nutritional feeding practices and stunting. The total R-Square value was 0.335, indicating that the three factors explained 33.5% of the variation in stunting. Socio-cultural factors and nutritional feeding practices play an important role in stunting among children under five in Mamuju City. A transcultural nursing approach should be strengthened through family-based nutrition education, local cultural sensitivity, and community leader involvement.